After Dickens : reading, adaptation, and performance - Glavin, John (Cambridge studies in nineteenth-century literature and culture, 1999)
After Dickens is both a performative reading of Dickens the novelist and an exploration of the potential for adaptive performance of the novels themselves. John Glavin conducts a historical inquiry into Dickens's relation to the theatre and theatricality of his own time, and uncovers a much more ambivalent, often hostile, relationship than has hitherto been noticed. In this context, Dickens's novels can be seen as a form of counter-performance, one which would allow the author to perform without being seen or scrutinized. But Glavin also explores the paradoxically rich performative potential in Dickens's fiction, and describes new ways to stage that fiction in emotionally powerful, critically acute adaptations.